Climate drives fire synchrony but local factors control fire regime change in northern Mexico. Issue 3 (2nd March 2017) - Yocom Kent, Larissa L.; Fulé, Peter Z.; Brown, Peter M.; Cerano‐Paredes, Julián; Cornejo‐Oviedo, Eladio; Cortés Montaño, Citlali; Drury, Stacy A.; Falk, Donald A.; Meunier, Jed; Poulos, Helen M.; Skinner, Carl N.; Stephens, Scott L.; et al.
Abstract: The occurrence of wildfire is influenced by a suite of factors ranging from "top‐down" influences (e.g., climate) to "bottom‐up" localized influences (e.g., ignitions, fuels, and land use). We carried out the first broad‐scale assessment of wildland fire patterns in northern Mexico to assess the relative influence of top‐down and bottom‐up drivers of fire in a region where frequent fire regimes continued well into the 20th century. Using a network of 67 sites, we assessed (1) fire synchrony and the scales at which synchrony is evident, (2) climate drivers of fire, and (3) asynchrony in fire regime changes. We found high fire synchrony across northern Mexico between 1750 and 2008, with synchrony highest at distances <400 km. Climate oscillations, especially El Niño‐Southern Oscillation, were important drivers of fire synchrony. However, bottom‐up factors modified fire occurrence at smaller spatial scales, with variable local influence on the timing of abrupt, unusually long fire‐free periods starting between 1887 and 1979 CE. Thirty sites lacked these fire‐free periods. In contrast to the neighboring southwestern United States, many ecosystems in northern Mexico maintain frequent fire regimes and intact fire–climate relationships that are useful in understanding climate influences on disturbance across scales of space and time.